The growth of Kappaphycus alvarezii under different depth and initial weight in Talengen waters, Sangihe Islands Regency - Tiwa, Richie B; Mondoringin, Lukas L.J.J; Salindeho, Indra N (e-Journal BUDIDAYA PERAIRAN, 2013)
The effect of depth and weight differences on early stage of seaweed growth Kappaphycus alvarezi was studied. This Research was conducted for over 42 days, from April to May 2013 in Talengen Waters, Regency Sangihe Islands, North Sulawesi. Experiment designed used was 4 x 3 factorial experiment in a completely randomized design, so there were two factors namely depth and weight. The depth factor (D) consisted of four levels and initial weight (W) consisted of three levels, thus there were 12 treatment combination: D1W1 (25 cm, 75 g), D1W2 (25 cm, 100 g), D1W3 (25 cm, 125 g), D2W1 (75 cm, 75 g), D2W2 (75 cm, 100 g), D2W3 (75 cm, 125 g), D3W1 (125 cm, 75 g), D3W2 (125 cm, 100 g), D3W3 ( 125 cm, 125 g), D4W1 (175 cm, 75 g), D4W2 (175 cm, 100 g), and D4W3 (175 cm, 125 g). Data collected were analyzed statistically using the statistical program JMP (SAS Institute). Statistical analysis showed there was a significant differences in relative growth of seaweed K. alvarezii (P> F.0003 <.01).The best relative growth of seaweed K. alvarezzi was achieved in treatment combination D1W1 (25 cm, 75 gr) as much as 302.89%. Keywords: Seaweed, Kappaphycus alvarezii, relative growth